Policies to Improve the Mental Health of People Influenced by COVID-19 in China: A Scoping Review - Qiu, Dan; Li, Yilu; Li, Ling; He, Jun; Ouyang, Feiyun; Xiao, Shuiyuan (Frontiers in Psychiatry, 2020)
Background: In response to the potentially concurrent mental health crisis during the COVID-19 outbreak, there have been ongoing mental health policies in China. This review aims to systematically synthesize the implemented national-level mental health policies released by the Chinese government during the COVID-19 outbreak, and summarize the implementation of those mental health policies. Methods: Six databases and two websites were systematically searched, including published studies and grey literature published between 1 December 2019 to 29 October 2020. Results: A total of 40 studies were included. Among them, 19 were national-level policies on mental health released by the Chinese government, and 21 studies reported data on implementation of those mental health policies. Mental health policies were issued for COVID-19 patients, suspected cases, medical staff, the general population, patients with mental illness, and mental institutions. In the early stage of the COVID-19 epidemic, attention was paid to psychological crisis intervention. In the later stage of the epidemic, the government focused mainly on psychological rehabilitation. During the COVID-19 outbreak, more than 500 psychiatrists from all over China were sent to Wuhan, about 625 hotlines were notified in 31 provinces, several online psychological consultation platforms have been established, social software such as Tiktok, Weibo, and WeChat were used for psychological education, and many books on mental health were published. Respond quickly, maximize the use of resources, emphasize the importance of policy evaluation and implementation quality were characteristics of mental health policies developed during the COVID-19 outbreak. Challenges facing China include low rate of mental health service utilization, lack of evaluation data on policy effects, has no existing national-level emergency response system and designated workforce to provide the psychological crisis interventions during a national emergency or disaster. Conclusions: This review suggests that China has responded quickly and comprehensively to the possible mental health crisis during the COVID-19 outbreak, appropriate mental health policies were released for different population. As the epidemic situation continues to change, the focus of mental health policies has been adjusted accordingly. However, we should noted that there is a lack of separate policies for specific mental health issues during the COVID-19 outbreak.